PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS KURIKULUM 2013 DAN PENDIDIKAN KARAKTER BAGI MAHASISWA PGSD FIP UNNES (Jurnal Kreatif : Jurnal Kependidikan Dasar, 2017)
In order to align the development of mathematics learning equipment in Elementary School Teacher Education (PGSD) so that it is in accordance with the 2013 curriculum and charactereducation, it is developed the learning equipment of mathematics based on the 2013 curriculum and character education for students of Elementary School Teacher Education (PGSD)Department at Semarang State University (UNNES). This was development research to produce mathematics learning equipment based on the 2013 curriculum and character education. The learning equipment development used 4-D model (four D model) by Thianggarajan. It was produced valid mathematics learning equipment in the Elementary School Teacher Education (PGSD) Departmentbased on the 2013 curriculum and character education character after going through the validation process made by some experts or specialists in the field of mathematics and the 2013 curriculum with the average value of 83.485%. The learning equipment included syllabus, Lecturing Unit (SAP), teaching materials, media, evaluation tool. The results of the development of mathematics learning equipment based on the 2013 and character education for students of Elementary School Teacher Education (PGSD) Department are valid, identified by: (1) The development of mathematics learning equipment based on the 2013 and character educationreached an average score of learning outcomes by 72.3. (2) The average score of learning outcomes in the experimental class using the mathematics learning equipment based on the 2013 and character educationis higher than the average score of learning outcomes in the control class implementing conventional learning.